The Effect of Exenatide Therapy in Previously Insulin-Treated Type 2 Diabetic Patients - Yasar, H (Acta endocrinologica (Bucharest, Romania : 2005), 2017)
To evaluate the effect of multiple daily injection (MDI) treatment replaced by Exenatide BID as compared with continuation of MDI. A total of 140 patients with type 2 diabetes, taking metformin and multiple daily insulin injections, were randomized to exenatide or insulin group that continued their insulin treatment. Patients were followed-up for 16 weeks. Blood glucose profiles, BMI, waist circumference, HbA1C, serum lipids and side effects were assesssed at weeks 0,12 and 16. There were no significant differences between the two groups with respect to baseline parameters. Glycemic control was similar between the two groups. The mean changes in HbA1C in exenatide group were -0.66±0.63% and in insulin group -0.74±0.92 % (p=0.594). In exenatide group, 59.6 % of patients and in insulin group 85.71 % of patients had maintained or improved glycemic control at the end of the study. In insulin group, insulin requirement increased 5.86 ± 4.46 units/day. Body weight and waist circumference decreased significantly in exenatide treatment group with respect to insulin group (p<0.001). Substituting exenatide for insulin might be an option in insulin-treated, type 2 diabetic patients having obesity, and poor glycemic control. However, patients with longer duration of diabetes and insulin treatment and with lower C-peptide levels might not benefit from exenatide therapy.